Tracking the Genealogical Reasoning Reconstruction of Nahdlatul Ulama (NU) Fiqh: From ‘Social Fiqh’ to ‘Civilization Fiqh’ - Reza Fauzi Nazar; Mohammad Fahmi Abdul Hamid (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
Fiqh, or in another term were called as Islamic jurisprudence, are the conceptions which are required by the Muslims to organize their interests in all aspects of life, provide the basics of the system of worship, administration, commerce, politics, social, and civilization. This article aims to trace and elaborate on the term